2021
DOI: 10.48550/arxiv.2105.07787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic structure of a generic null surface and the zeroth law in scalar-tensor theory

Sumit Dey,
Krishnakanta Bhattacharya,
Bibhas Ranjan Majhi

Abstract: We show that the equation of motion of scalar-tensor theory, along the likes of GR and its higher order generalization i.e Lanczos-Lovelock gravity, acquires thermodynamic identity when projected on a generic null surface. The relevant projection is given by E ab l a k b , whereab represents the equation motion for gravitational field in presence of external matter, l a is the generator of the null surface and k a is the corresponding auxiliary null vector. Our analysis is done completely in a covariant way. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…These theories can be described in either Jordan frame or in Einstein frame, which are conformally connected to each other. The physical equivalence of two conformal frames is a longstanding debate in literature [19,28,[33][34][35][36]. However, in our earlier work [19,[33][34][35][36], we have shown that the thermodynamic parameters, like entropy, temperature, internal energy (which is given by the mass of the black hole), angular momentum etc.…”
Section: Rn-ads Black Hole In D Spacetime Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations
“…These theories can be described in either Jordan frame or in Einstein frame, which are conformally connected to each other. The physical equivalence of two conformal frames is a longstanding debate in literature [19,28,[33][34][35][36]. However, in our earlier work [19,[33][34][35][36], we have shown that the thermodynamic parameters, like entropy, temperature, internal energy (which is given by the mass of the black hole), angular momentum etc.…”
Section: Rn-ads Black Hole In D Spacetime Dimensionsmentioning
confidence: 99%
“…The above identity (38) will help us to obtain off-shell Noether current and potential due to the diffeomorphism invariance. Firstly, we want to obtain the change of the Lagrangian due to the diffeomorphism invariance x a −→ x a + ξ a , which can be obtained by replacing arbitrary variation δ in (36) by Lie derivative (£ ξ ). Thus, (36) yields…”
Section: Rn-ads Black Hole In D Spacetime Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidentally, one can provide a thermodynamical interpretation of a gravitational field equation by suitably projecting it on a generic null surface also [16][17][18][19][20][21]. For instance, Einstein's equation, contracted with null generator and corresponding auxiliary vector, yields a thermodynamical identity of the form T δ λ S = δ λ E + P δ λ V [16][17][18][19], where symbols have their usual meanings and the variation can be interpreted as the change due to virtual displacement of the null surface along an auxiliary null vector, parametrized by the parameter λ (generalization to Lanczos-Lovelock gravity [22] and scalartensor theory [23] has been done as well). Therefore, it has been realized that null surfaces which act as one-way membranes to a certain class of observers also possess thermodynamical attributions.…”
Section: Introductionmentioning
confidence: 99%